Analisis pengaruh motivasi dan kepuasan kerja terhadap kinerja karyawan - Tulus Rohana (Insight Management Journal, 2021)
The purpose of this study was to effect Analysis of Work Environment Motivation and Job Satisfaction of Employee Performance. The analytical method used is descriptive method with a quantitative approach and the multiple correlation and multiple regression using SPSS version 20.0. Based on the results of data analysis equations. Based on hypothesis testing using t test that the style of Work Environment Motivation and Job Satisfaction positif and significant impact of motivation on employee performance. Results of studies simultaneously using the F test, indicating that all of the independent variables significantly affect the performance of employees. Rated R Square of 0.254 which means that the effect of variable X (motivation and job satisfaction) to variable Y (employee performance) is at 25,4% while the remaining 25,3% influenced by other variables beyond the variables studied.